2017
DOI: 10.1186/s13104-017-2696-4
|View full text |Cite
|
Sign up to set email alerts
|

The in vitro effects of interferon-gamma, alone or in combination with amphotericin B, tested against the pathogenic fungi Candida albicans and Aspergillus fumigatus

Abstract: ObjectiveRecent studies into the antifungal activity of NK-cells against the Aspergillus fumigatus have presented differing accounts on their mode of antifungal activity. One of these mechanisms proposed that NK-cells may kill the fungus via the direct effects of exposure to Interferon gamma (IFN-γ).ResultsIn this study we investigated the direct antifungal effects of recombinant human IFN-γ against a range of pathogenic fungi by measuring cellular damage using an XTT-based assay and cell viability through pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…As higher concentrations of IFN-γ, e.g., 50 or 100 pg/ml, did not increase antifungal activity, and IFN-γ serum levels of 18 ± 30 pg/ml can be detected in healthy individuals ( 94 ), the importance of the direct antifungal effect in vivo is questionable. Corroborating the data of another report ( 70 ), no significant antifungal effects of IFN-γ were detected in Candida and C. neoformans ( 93 ). However, it is important to note that a combination of amphotericin B at a concentration of 1 µg/ml and IFN-γ at 32 pg/ml increased the efficacy of amphotericin B against A. fumigatus , which might be important for immunotherapeutic strategies.…”
Section: Direct Damage Of Fungal Pathogens By Nk Cellssupporting
confidence: 67%
See 1 more Smart Citation
“…As higher concentrations of IFN-γ, e.g., 50 or 100 pg/ml, did not increase antifungal activity, and IFN-γ serum levels of 18 ± 30 pg/ml can be detected in healthy individuals ( 94 ), the importance of the direct antifungal effect in vivo is questionable. Corroborating the data of another report ( 70 ), no significant antifungal effects of IFN-γ were detected in Candida and C. neoformans ( 93 ). However, it is important to note that a combination of amphotericin B at a concentration of 1 µg/ml and IFN-γ at 32 pg/ml increased the efficacy of amphotericin B against A. fumigatus , which might be important for immunotherapeutic strategies.…”
Section: Direct Damage Of Fungal Pathogens By Nk Cellssupporting
confidence: 67%
“…The authors suggested as explanation that “IFN-γ might cooperate with fungal ribotoxins, (…), transforming them into suicide molecules for fungus” ( 65 ). Similarly, it was demonstrated that IFN-γ at a concentration of 32 pg/ml exhibited a small but significant antifungal effect on A. fumigatus, A. flavus , and Saccharomyces cerevisiae , and inhibited the growth by 6, 11, and 17%, respectively ( 93 ). As higher concentrations of IFN-γ, e.g., 50 or 100 pg/ml, did not increase antifungal activity, and IFN-γ serum levels of 18 ± 30 pg/ml can be detected in healthy individuals ( 94 ), the importance of the direct antifungal effect in vivo is questionable.…”
Section: Direct Damage Of Fungal Pathogens By Nk Cellsmentioning
confidence: 99%
“…Even so, IFN-γ has recently been used as an adjunctive therapy against fungal infection, 25,26 though treatment with IFN-γ alone was not effective. 27 Although IL-17 has been suggested to play a key role in Candida eradication, its role is restricted to mucosal infections. 28 Furthermore, our recent investigation demonstrated that IFN-γ, but not IL-17, was a significant protective cytokine for host defense against secondary fungal infection in murine sepsis.…”
Section: Discussionmentioning
confidence: 99%
“…Minimum inhibitory concentrations (MICs) of several antifungal drugs were determined using Yeast Sensititre YO10 plates (ThermoFisher Scientific) as per the manufacturer's instructions [78]. In brief, fungal conidia were added to the included broth as described in the manufacturer's instructions to achieve a density of 1.5-8 × 10 3 cells/mL; 100 µL of broth containing conidia was added to each well of the YO10 Sensititre plate (Ther-moFisher Scientific).…”
Section: Mic Determinationsmentioning
confidence: 99%